Automatic temperature detector to mitigate the spread of COVID-19 - Prajna Deshanta Ibnugraha; Rini Handayani; Khamla NonAlinsavath (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The COVID-19 causes wide impact in business operation. The enterprise must mitigate the risk of COVID-19 spread in its environment. The monitoring of body temperature for employees can be applied as a method to prevent COVID-19 spread. However, the monitoring system must consider several factors such as contactless system, accountable, and simple. The integration between IR temperature sensor and attendance system based on ESP32 is able to provide those need. The use of proximity, IR, and RFID sensor is affordable to detect body temperature properly within 10 cm. The proposed system provides notification if user gets fever or suspect of COVID-19 by detecting the body temperature. The accuracy of sensor is adequate. It is based on the comparison testing between proposed system with body thermometer where the testing is performed 30 times for each condition. In order to deduce the comparison result, this study uses analysis of variance method. The analysis produces F-critical (4,006) greater than F-value (0,022) where it means that the proposed system and body thermometer have similar testing result. It is shown good accuracy for the proposed system.